MODE OF ACTION OF AN AYURVEDIC PREPARATION IN RELIEVING SIGN AND SYMPTOMS OF MADATYAYA: A CONCEPTUAL STUDY - Kumar Satbir, *Chawla; Dr, Priyanka (International Journal of Ayurveda and Pharma Research, 2017)
Madatyaya (Alcoholism) which is a global problem in present world and it is also well described in ancient Indian classical texts. As per the Ayurvedic text Madatyaya is a Tridoshaja Vyadhi (Disease)and in contemporary science it can be correlated with Alcoholism. The withdrawal symptoms of alcoholism are the biggest hurdle in overcoming this disease. Once the sign and symptoms of withdrawal of madatyaya are controlled the disease can be treated easily and it will help the patient to give up the addiction of alcohol easily. The present study is a conceptual work to illustrate the mode of action of â€œPunarnavadi Ghrittâ€ in reliving the withdrawal symptom of Madatyaya. In Ayurveda many preparations were mentioned for treatment of Madatyaya. But the contents of Punarnavadi Ghritt have Tridosha shamaka effect on all the three Vikrit doshas in Madatyaya. The present conceptual study describes the mode of action of contents of Punarnavadi Ghrittaon the basis of Rasa, Guna, Virya, Vipaka, Karma and Doshsghanta in suppressing the sign and symptoms of withdrawal of Madatyaya. The mode of action of every content of Punarnavadi Ghritta is explained systematically that how it suppress the sign and symptoms and works on Samprapti vighatan (to breakdown the pathogenesis) of Madatyaya. Once the pathogenesis is hampered it is easy to treat the disease. The study reviles the probable mode of action of Punarnavadi Ghrittaon Madatyaya which will help to treat the alcohol addicted patients.